Compact circularly polarized inset-fed circular microstrip antenna for 5 GHz band. (January 2018) - Kingsuwannaphong, Thoetphan; Sittakul, Vitawat
Abstract: This paper proposes a compact circularly polarized microstrip antenna with Left-Hand Circular Polarization (LHCP) property for wireless communication system at 5.7 GHz (U-NII 5 GHz band). In this design, a tapered-slot is included and it can act as the second signal source of the antenna to generate circular polarization property and this can remove the need of the external second signal source. The axial ratio of ∼2 and the radiation pattern results prove that the designed antenna meets the LHCP criteria. Moreover, the inset feeder is selected and it demonstrates the improvement on bandwidth and input impedance of the antenna.